On Exact Solutions of Nonlinear Diffusion Equations - Barannyk, A. F.; Yuryk, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
New classes of the exact solutions of nonlinear diffusion equations are constructed.